If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2y = 4(y + -1) Reorder the terms: 6 + 2y = 4(-1 + y) 6 + 2y = (-1 * 4 + y * 4) 6 + 2y = (-4 + 4y) Solving 6 + 2y = -4 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 6 + 2y + -4y = -4 + 4y + -4y Combine like terms: 2y + -4y = -2y 6 + -2y = -4 + 4y + -4y Combine like terms: 4y + -4y = 0 6 + -2y = -4 + 0 6 + -2y = -4 Add '-6' to each side of the equation. 6 + -6 + -2y = -4 + -6 Combine like terms: 6 + -6 = 0 0 + -2y = -4 + -6 -2y = -4 + -6 Combine like terms: -4 + -6 = -10 -2y = -10 Divide each side by '-2'. y = 5 Simplifying y = 5
| 2.5x-1.5x=1500 | | (.3x-1.34)=y | | -12=-4523+2y | | x(sec^2x+1)=0 | | 5x+3-5x=15 | | 2(5x-1)=58 | | 3(7+2x)=51 | | 4(2x+8)=56 | | 3(4+2x)=30 | | 3x^0+4y^3= | | 2(4x+4)=32 | | 4[x-4/4x-1] | | s^2+8s+16-81=0 | | 5x+0.25y+0.75z=100 | | 4*x-3*y=2 | | 3(d+4)=8(-3) | | A=2(3.14) | | 70=-16t^2+vot+70o | | 2M+3n=7mn | | 2x^4+4x+2=0 | | 6x=6x+0 | | 4x+xy= | | y^2=4(ky-2)-4 | | 25*x^4+8001*x^3+40320*x^2+1200*x-400=0 | | -8x^2+8x+30=0 | | 4x^2-30x+10=0 | | -5x-2(7x-17)=80 | | 12+5x=7(x-2) | | 8p-5=19 | | .5t+36=15 | | x^2+4x-100000000=0 | | 30-(30-2h)=2h |